Endoscopic decompressive surgery for lumbar spinal stenosis : analysis of clinical outcome and predictive factors - Salim, Azizul Akram (2016)
BACKGROUND CONTEXT : Endoscopic approach is one of the approaches that maintained the aim of surgery while minimize the collateral tissue destruction. Its efficacy and safety have been advocated by numerous studies. To our knowledge, there are number of studies done for lumbar stenosis with regards to the outcome and related issues in endoscopic spine surgery, however there are lacked of literature that evaluate the outcome of the decompressive lumbar spine surgery. PURPOSE : To assess the outcome result of endoscopic surgery for lumbar stenosis and to determine it’s predictive factors . STUDY DESIGN : A retrospective cohort study of patients with degenerative lumbar spinal stenosis who underwent endoscopic percutaneous surgery using unilateral approach for bilateral decompression. PATIENT SAMPLE : Sixty patients with lumbar spinal stenosis underwent endoscopic decompressive surgery between 2009 and 2013. METHODS : Between 2009 and 2013, 60 eligible patients who undergone endoscopic interlaminar decompressive spine surgery (Destandau’s method) for lumbar degenerative spinal stenosis in Hospital Universiti Sains Malaysia were selected for the study. The clinical outcome was measured pre and post-operative for Visual Analogue Scale (VAS) for back and leg pain, motor grading, sensory, Oswestry Disability Index (ODI), and MacNab’s criteria. The cohort was group into two categories: excellent to good result was grouped into favourable category and fair to poor result was grouped into unfavourable category. Paired t-test and Fisher exact test was used for statistical analysis. RESULTS : Mean age of patients were 60.82 years old. The mean follow-up period was 30.1 months (range 17.2 to 43 months). There were 23 (38.3%) male and 37 (61.7%) female. The mean operation time was 183.6 minutes (ranging from 124.8 minutes to 242.4 minutes). Mean blood loss was 150.18ml (ranging from 30.82 ml to 269.54 ml). Post-operative hospital stay mean was 2.45 days (ranging from 1.34 days to 3.56 days). Most frequently involved level were L4/L5 in 51 patients (52.6%), followed by L3/L4 in 19 patients (19.6%), L5/S1 in 24 patients (24.7%), and L2/L3 in 3 patients (3.1%). VAS for back pain and leg pain and ODI for pre and post operation was statistically significant (p<0.001). Reduction in neurology is statistically insignificant. Based on Macnab’s criteria, 88.4% showed excellent to good outcome and 11.7% showed fair outcome. There was no significant predicitive factor for the outcome. As for complication, 13.3% of patients had dural tear; 1.6% had nerve root injury, wrong level and delay wound healing; 11.6 % had leg dysesthesia; 11.6% had recurrent stenosis; and 1.6% and 6.6% had reduced motor and sensory respectively.. CONCLUSIONS : Endoscopic decompressive lumbar stenosis surgery is a safe surgery. It has an excellent outcome in term of reducing the back and leg pain, and improve quality of life beside a shorter hospital stay and early mobilization.